Effect of Minerals on Penicillin Production by Penicillium chrysogenum Strains Isolated from Coastal Marshes of Tamilnadu - Reena, Dr. A (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACT Several studies revealed that mineral nutrients, including microelements, could stimulate the secondary metabolism in fungi. The importance of mineral elements in the production of penicillin was studied from three wild strains of Penicillium chrysogenum (MPPS1, MPPS2 and MPPS3), isolated from marsh soils of Muthupet coast, Tamilnadu. P. chrysogenum strains were cultured in PDA medium to evaluate their penicillin productivity levels after substituting different minerals (Mgso4, ZnSo4, KH2Po4). The results showed remarkable variations in the levels of penicillin productivity among the minerals and the strains. Among the three inorganic minerals used to test the optimum penicillin productivity by the three strains of P. chrysogenum, K2HPO4 showed higher productivity levels at 120h of fermentation period (P. chrysogenum MPPS1: 398.63 unit/ml; MPPS2: 442.60 unit/ml; MPPS3: 387.64 unit/ml). The penicillin production was comparatively low in the culture supernatants of MgSo4.7H2O treated cultures. Optimum penicillin productivity was observed at 120h of fermentation period with all the three strains of P. chrysogenum (MPPS1: 392.24 unit/ml; MPPS2: 398.64 unit/ml; MPPS3: 380.22 unit/ml). The penicillin productivity data showed that zinc exhibited a moderate effect on penicillin production with all the three P. chrysogenum strains (MPPS1, MPPS2 and MPPS3). Penicillin production is increasing up to 394.16 unit/ml in the MPPS2 strain, when compared to MPPS1 (367.48 unit/ml) and MPPS3 (336.28 unit/ml) strains. The pH levels of the culture media treated with MgSo4.7H2O, K2HPO4 and ZnSo4 are exhibiting similar trends in their increase towards alkalinity, during the course of fermentation period.